Power distance in India: Paternalism, religion and caste: some issues surrounding the implementation of lean production techniques - Kunju Kunju Mathew, Sagi; Taylor, Greig (Emerald, 2018)
Purpose: The purpose of this paper is to explore how cultural differentiation can affect the successful transplantation of lean management and production techniques from the parent country to subsidiary countries in the developing world. In particular, the focus will be on car manufacture in India and the role of hierarchy in Indian society, with reflection on how this seeps into workplace and power relations. Design/methodology/approach: Lean production techniques have been hailed as revolutionising modern manufacturing, particularly in the automotive sector. In developed world countries, car manufacturers have made significant gains in efficiency and productivity as a result of their implementation. However, as many of these multinational companies (MNCs) have expanded production into rapidly-developing nations to take advantage of both their market and low-labour costs, the introduction of lean production practices have met some resistance. This is because certain underpinning concepts and values of the lean system, such as team work, delegation of authority and upward communication can be considered incompatible with aspects of local culture and employees’ attitude towards work and their superiors. The analysis presented is based on a series of semi-structured interviews with managers and workers from an India-based subsidiary of a MNC car manufacturer and engagement with the existing literature. Findings: It concludes that paternal relationships, religious values and group orientation in Indian society have a significant impact on the dynamics of the workplace and result in a brand of power distance that is specific to this national context, raising questions about the suitability of universal implementation of lean production practices. Originality/value: “Power distance” has become a catch-all term for cultures with an orientation towards hierarchy and status in society. However, this categorisation masks some of the factors belying the phenomenon and intricacies relating to how it plays out in the workplace. It is simplistic to postulate that high power distance cultures might be incompatible with management approaches that decentralise authority and increase worker participation. Rather than rely on over-generalisations, the analysis provided has attempted to deconstruct the composition of power distance in the Indian context and document systematically how features of Indian culture conflict with the principles of lean production techniques, using a case study from an Indian subsidiary of a MNC. In particular, the study finds that religion, caste and paternalism create an India-specific power distance that manifests itself in worker behaviour and workplace relationships.